Social and Psychological Dimensions of Personal Debt and the Debt Industry
XVIII, 304 p. 7 illus.
Keywords: An understanding of personal debt requires an understanding of the complex social systems that produce poverty. By drawing upon international perspectives, this book investigates why more and more people are in debt, why it is causing so much mental distress and exactly who is benefiting from what has become the world's number one growth industry.